Technology Adoption and Competitive Advantage: The Role of Digital Payments in Tourism MSME Performance - Kristi Arina; Elsje Lintong; Sammy Korua; Joni Kutu' Kampilong; Afriti Salasa; Indah Kembuan (SOSIOEDUKASI, 2025)
This study investigates the impact of the digital payment adoption on the business performance of the tourism micro, small, and medium enterprises (MSMEs) in the Likupang Special Economic Zone of Indonesia. Using a combination of the Technology Acceptance Model, the Resource-Based View, Dynamic Capability Theory, and Institutional Theory, the study examines survey data from 284 MSMEs and 18 stakeholder interviews. Results show that perceived usefulness and ease of use are essential factors for adoption. In addition, the greater the adoption of digital payments within the organization, the stronger the organizational capabilities (β = 0.41), which positively affect competitive advantage (β = 0.38) and, subsequently, business performance (β = 0.33). Network reliability, transparent merchant discount rates, and successful onboarding are institutional facilitators that significantly moderate the adoption-performance relationship (β = 0.12, p = 0.009). Sub-sectoral analysis reveals that accommodation and food and beverage have the highest transaction intensity and service integration, enabling substantial benefits, whereas transformations in transport and retail are minimal. The study shows that the strategic value of digital payments can be generated only if they are part of dynamic capacity-building processes and underpinned by facilitating institutional conditions. These understandings refute simplistic assumptions that adoption equals performance and emphasize the necessity of digital inclusion policies that are more tailored and ecosystem-sensitive in emerging tourist economies